Conclusions and recommendations - Antongiovanni M. (Exploitation of Mediterranean roughage and by-products, 1998)
The most relevant results obtained from the co-operation work of the project are reviewed and commented. It is concluded that one can choose between treating and not treating fibrous feeds. In this latter case, attention must be paid to the correct association with a protein feed, both qualitatively and quantitatively.